Prevalence and Mean Intensity of Nematode Parasites in Anurans of the Genus Sclerophrys in Burkina Faso (West Africa) - Soubeiga, Patricia; Boungou, Magloire; Thiombiano, Gabiliga Noel; Chabi, Adechegoun Meschac Bertrand; Zougouri, Nakoula Emile; Ouedraogo, Nazeguenimba Armel; Bagayan, Mohamed; Sinare, Yamba (European Scientific Journal, ESJ, 2025)
As part of a study aimed at improving understanding of parasitic infections in anurans for their conservation in Burkina Faso, a survey was conducted on nematode parasites infecting anurans of the genus Sclerophrys between June 2022 and November 2023 in the provinces of Ganzourgou, Kadiogo, and Houet. Anurans were collected at night using the Visual and Acoustic Encounter Survey (VAES) method, then dissected and examined for nematode infections. A total of 743 individuals of the genus Sclerophrys (family Bufonidae) were examined, with 669 found to be infected, resulting in an overall prevalence of 90.04%. Seasonal prevalence was 87.94% during the rainy season and 92.35% during the dry season, with the difference being statistically significant (p < 0.05). Nine nematode species were identified: Amplicaecum pesteri, Cosmocerca ornata, Oswaldocruzia sp., Physaloptera sp., Rhabdias africanus, Rhabdias sp., Cosmocercella sp., Cosmocercoides sp., and Aplectana sp. The most prevalent species was Cosmocercoides sp. (58.95%), while Cosmocerca ornata was the least prevalent (0.26%). This study provides significant insights into the Sclerophrys anurans population and their nematode parasites. Four Bufonidae toad species— Sclerophrys maculata, S. regularis, S. pentoni, and Sclerophrys xeros—were found to be infested by these nine nematode species. The high overall prevalence indicates a significant parasitic burden in these Sclerophrys toads. Furthermore, the parasitic load was notably higher in environments with increased pollution from chemical fertilizer use.